BUSINESS COMMUNICATION STRATEGY OF DPP HIPMIKINDO - JAKARTA IN IMPROVING HUMAN RESOURCE OF JABODETABEK MSMES - Agus Jatmika; Harmonis Harmonis (UNIVERSITAS PAKUAN, 2021)
The management of Hipmikindo, which consists of people with high business perspectives, is certainly well aware that the resources of MSME entrepreneurs are still uncompetitiveness. The culture of small entrepreneurs who are very pragmatic, looking at business as just a matter of selling, certainly becomes an obstacle to progress and develop “capacity building”. Even more, if the use of technology is responded as a